Myxococcus xanthus predation: an updated overview - Contreras-Moreno, Francisco Javier; Pérez, Juana; Muñoz-Dorado, José; Moraleda-Muñoz, Aurelio; Marcos-Torres, Francisco Javier (Frontiers in Microbiology, 2024)
Bacterial predators are widely distributed across a variety of natural environments. Understanding predatory interactions is of great importance since they play a defining role in shaping microbial communities in habitats such as soils. Myxococcus xanthus is a soil-dwelling bacterial predator that can prey on Gram-positive and Gram-negative bacteria and even on eukaryotic microorganisms. This model organism has been studied for many decades for its unusual lifecycle, characterized by the formation of multicellular fruiting bodies filled with myxospores. However, less is known about its predatory behavior despite being an integral part of its lifecycle. Predation in M. xanthus is a multifactorial process that involves several mechanisms working synergistically, including motility systems to efficiently track and hunt prey, and a combination of short-range and contact-dependent mechanisms to achieve prey death and feed on them. In the short-range attack, M. xanthus is best known for the collective production of secondary metabolites and hydrolytic enzymes to kill prey and degrade cellular components. On the other hand, contact-dependent killing is a cell-to-cell process that relies on Tad-like and type III secretion systems. Furthermore, recent research has revealed that metals also play an important role during predation, either by inducing oxidative stress in the prey, or by competing for essential metals. In this paper, we review the current knowledge about M. xanthus predation, focusing on the different mechanisms used to hunt, kill, and feed on its prey, considering the most recent discoveries and the transcriptomic data available.